Study on the structural stability evaluation of umbilical winch for ROV LARS. Issue 1 (5th March 2018) - Woo, Namsub; Han, Sangmok; Kim, Youngju; Huh, Sunchul; Kim, Hyunji
Abstract : Purpose: The purpose of this study is structural stability evaluation of umbilical winch. In accordance with the recent trend for developing natural resources, high-technology equipment on exploration ships is becoming more technologically advanced. One such piece of high-technology equipment is the umbilical winch. In this study, the umbilical winch is divided into two parts (drum and winch), where each is respectively designed with three dimensional models using CATIA, and dynamic simulation and structural analysis are performed using ANSYS. Design/methodology/approach: In this paper, the winch is divided into two parts for finite element analysis, the drum and whole winch model, and the parts are designed as three-dimensional models except for some small parts, such as bolt holes. Dynamic simulation and structural analysis are then performed using ANSYS. The analysis results ensure the reliability of the design methods and will be used in the domestic localization of remote operated vehicle (ROV) launch and recovery systems (LARS). Findings: The strain is identified from the results, but it is very small. Some stress is concentrated at the lower corner of the drum, but the maximum stress value is lower than the allowable stress; therefore, the structure has no impact on the strain and stress. Thus, it is determined that the designed structure is safe. The results ensure the reliability of the design methods and will be used in the domestic localization of ROV LARS. Originality/value: Previous studies focus on the static and mechanic problems of the winch by considering winch and drum breakage in the umbilical winch system. However, ships have a nonlinear motion characteristic with six degrees of freedom according to the constant influence of the external environment. In addition, from a design perspective, the dynamic characteristics (e.g. the ship's motions) are more important than the static characteristics. Thus, the authors focus on winch stability securement with variable loads, such as ships moving, wave disturbance and other such important environment conditions.